The Restructuring of Social Inequalities During the COVID-19 Pandemic in Australia - Chesters, Jenny (Socialinė teorija, empirija, politika ir praktika, 2024)
As the COVID-19 virus began to spread across Australia, a six-week national lockdown was implemented in late March 2020. Australians were largely confined to their homes and nonessential economic and social activities ceased. Subsequently, lockdowns were implemented at various times in various states, territories and regions in response to local outbreaks of the virus. To examine how the restrictions associated with the pandemic impacted on the working lives of young Australians during the 2020 lockdowns, I draw on Life Patterns project data generated from semistructured interviews conducted with 40 participants in September and October 2020. From a class perspective, the lockdowns exacerbated existing inequalities related to occupation. Some participants, such as those in the hospitality sector, were stood down whereas other participants either worked from home (e.g., professionals and white-collar workers) or continued working as usual after being classified as essential workers (e.g., nurses, doctors, security guards). Participants who were stood down immediately were left to fend for themselves until the Federal Government introduced JobKeeper payments. They had to rely on their annual leave, withdraw money from their retirement savings and/ or move in with family or friends just to survive. Participants who were able to keep working saved money due to being confined to home and not be able to socialise or take holidays. Consequently, due to the COVID-19 pandemic, some participants depleted their savings whereas others had built on their existing wealth.
Keywords: Australia; COVID-19; Inequality; Precarious work